Sustainable Supply Chain Management through Compliance of Stakeholders’ Requirements: A Study on Ready-Made Garment (RMG) Industry of Bangladesh - Chowdhury, Md. Maruf Hossan; Dewan, Mohammed Naim A.; Quaddus, Mohammed (PACIS, 2013)
Sustainability in supply chain is now an issue of concurrent focus, as stakeholders are demanding sustainability from the point of production to the point of consumption. Research on sustainable supply chain management (SSCM) is not substantial in number. Most of the studies concentrate on social, environmental, and economic aspects of supply chain in a standalone fashion. Further, previous studies are dominantly conceptual in nature. Comprehensive empirical research on sustainable supply chain management incorporating social, environmental and economic aspects is very rare. Upon existence of such void in the literature this study aims at developing a comprehensive SSCM framework in the context of RMG supply chain of Bangladesh. An exploratory field study utilizing an inductive methodology involving a multiple-case study approach has been undertaken. Data have been collected by conducting face to face interviews with 15 decision makers of RMG manufacturing companies and their suppliers. We utilize content analysis techniques with a view to identify the factors with their associated. It is novel in the research findings that, apart from compliance of the triple bottom line components, compliance of buyers’ operational requirements and sustainability governance are also important components of RMG supply chain sustainability. Further, some important interrelationships among sustainability factors have been explored. Finally, based on the extracted sustainability components and their interrelationships an integrated SSCM model has been developed.